Amphibia, anura, hylidae, hypsiboas raniceps cope, 1862: Distribution extension - Zina, Juliana; de Sá, Fábio Perin [UNESP]; Prado, Cynthia A. P. [UNESP] (My University, 2010)
Hypsiboas raniceps is a large treefrog typically found in the Cerrado and Caatinga biomes. Here we provide information about new records of this species in the Atlantic Forest and raise some hypotheses that could explain the late record of this species in this biome. © 2010 Check List and Authors.
Keywords: Amphibia; Anura; Hylidae; Raniceps